Imagined Germany Richard Wagner's National Utopia, Second Edition - Salmi, Hannu (Peter Lang International Academic Publishing Group, 2020)
Richard Wagner (1813-1883) has often been regarded as a symbol of "Germanness." Despite this view, few studies have been undertaken regarding his nationalistic thinking. Imagined Germany focuses on Wagner's idea of Deutschtum, especially during the unification of Germany, 1864-1871. Salmi discusses how Wagner defined Germanness, what stereotypes, ideas, and sentiments he attached to it, and what kind of state could realize Wagner's national ideals.